1997
DOI: 10.1123/ssj.14.4.362
|View full text |Cite
|
Sign up to set email alerts
|

A Sociology of North American Sociology of Sport: Disunity in Unity, 1965 to 1996

Abstract: As we pass the 30th anniversary of a recognized sociology of sport in North America, it is appropriate to develop a current sociological analysis of the subdiscipline. In the first part we examine the origins of the field and the development of the Wisconsin socialization paradigm and the social problems perspective. In the second part we explore the critical shift in the field, emerging from an engagement with C. Wright Mills, and the development of a political economy perspective. In the third part we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Writing in the IRSS, Coakley (1987: 76) suggested that, based on a content summary of papers published in the first 14 issues of the SSJ, 'American authors show that sociology of sport research in the United States emphasises descriptive and 'issue-related' quantitative studies rather than qualitative or theory based studies'. Others have tracked the evolution of the sociology of sport as a sub-discipline (Atkinson, 2011;Ingham and Donnelly, 1997;Krawczyk, 1990;Loy and Sage, 1997;McPherson, 1975;Rowe et al, 1997;Silk and Andrews, 2011;Silk et al, 2010), its related professional associations and conferences (Greendorfer, 1987;Melnick and Sabo, 1987), with Nixon's (2010) commentary on the relationship between North American Society for the Sociology of Sport (NASSS) and academic programmes of study in the USA being a recent contribution.…”
mentioning
confidence: 99%
“…Writing in the IRSS, Coakley (1987: 76) suggested that, based on a content summary of papers published in the first 14 issues of the SSJ, 'American authors show that sociology of sport research in the United States emphasises descriptive and 'issue-related' quantitative studies rather than qualitative or theory based studies'. Others have tracked the evolution of the sociology of sport as a sub-discipline (Atkinson, 2011;Ingham and Donnelly, 1997;Krawczyk, 1990;Loy and Sage, 1997;McPherson, 1975;Rowe et al, 1997;Silk and Andrews, 2011;Silk et al, 2010), its related professional associations and conferences (Greendorfer, 1987;Melnick and Sabo, 1987), with Nixon's (2010) commentary on the relationship between North American Society for the Sociology of Sport (NASSS) and academic programmes of study in the USA being a recent contribution.…”
mentioning
confidence: 99%
“…Moreover, when Snyder and Spreitzer presented an outline of research in the field in 1974, two of the five areas they highlighted ('small groups' and 'social-psychological aspects') would, with the passing of 23 time, become more firmly situated within psychology. Sage's (1981) overview, andDonnelly's (1997) more recent account, demonstrate a similar division, with one ('sport as a subsystem') of three themes, and two ('socialization' and 'group dynamics') of seven themes respectively, becoming topics which would ultimately be partly or wholly positioned outside the subdiscipline.…”
Section: Disciplinary Breadthmentioning
confidence: 99%
“…In their overviews of the field Snyder andSprietzer (1974/1980), Lüschen and Sage (1981), and Ingham and Donnelly (1997) all cite something akin to 'definitional attempts' as among the main strands of literature in the emergent field. Loy (1968), Lüschen (1970) Edwards (1973) and Ingham and Loy (1973) are identified as amongst the key works.…”
Section: Scope Of Analysismentioning
confidence: 99%
See 2 more Smart Citations